Impact properties of oil palm empty fruit bunch filled impact modified unplasticised poly (vinyl chloride) composites - Abu Bakar, Aznizam; Hassan, Azman (Penerbit UTM Press, 2003)
Oil palm empty fruit bunch (EFB) reinforced composite is an emerging area in polymer technology. EFB is a low cost filler with low density, high specific properties as well as being nonabrasive. This type of composites offers several advantages comparable to those of conventional fiber composites. The main objective of the investigation reported in this paper is to study the effect of EFB filler loading and impact modifiers, namely chlorinated polyethylene (CPE) and acrylic on the mechanical properties of EFB filled-PVC-U composites. In preparing the samples, the PVC-U resins and the additives were initially dry blended using a laboratory blender before being milled into sheets using a two-roll mill. Test specimens were prepared using a hot press and impact tested using a pendulum type machine according to Izod mode. The results from the impact test showed that the unfilled PVC-U samples of both impact modifiers changes from brittle to ductile mode with increasing impact modifier concentration. The incorporation of EFB into unmodified PVC-U and modified PVCU has resulted in the reduction of impact strength. As the EFB filler content increases from to 10 to 40 phr, impact strength reduction of about 40% and 30% was observed for acrylic-modified PVC-U and CPE-modified PVC-U, respectively. The impact strength reduction was only marginal for unmodified PVC-U composites. The detrimental effect of fillers on the impact performance was due to the volume taken up. Fillers unlike the matrix are incapable of dissipating stress through the mechanisms known as shear yielding prior to fracture. The impact modifier was found to be effective in enhancing the impact strength of EFB-filled PVC-U composites. However, the effectiveness decreases with increasing filler loadings. The impact strength of CPE-modified PVC-U was higher than acrylic-modified PVCU at filler loading at 20 phr and higher.